Communicating The Collaborative Lecturing Style to Millenial Learner in The Classroom - Lucy Pujasari Supratman; Aep Wahyudin (Faculty of Social and Political Science, Universitas Muhammadiyah Tangerang, 2021)
One-way communication learning is no longer relevant for millennial learners. This digital native generation need the independency to learn things. They need to be understood by their unique characteristics. The problems arise when lecturers are still applying conventional teaching which results in millennial learner’s dissatisfaction. Thus, the lecturers faced challenges to change their lecturing style to facilitate millennial needs at class. The purpose of the research is to analyze the lecturing communication style using collaborative model based on millennial learner’s perspective. Telkom University was chosen due to its achievement as first best private university along with many international accreditations in Indonesia. The informants who participated were 30 international class students aged 18-19 years in the first batch semester. The author conducted focus group discussion which were recorded through online zoom. The results of the study found that millennial learner styles wanted intellectual experiences, emotional experiences and technological experiences through collaborative learning style in their learning activities. Furthermore, these students expect four lecturing communication style, such as sense of humor lecturer, interactive, video usage and put in student shoes. Applying lecturer communication style based on these three experiences through collaboration model and lecturing communication style would increase the active participation of millennial learners.Keywords: Communication, collaboration model, lecturing style, millennial learner ABSTRAK Pengajaran satu arah sudah tidak relevan lagi bagi mahasiswa milenial. Generasi digital ini membutuhkan pembelajaran yang mandiri. Mereka ingin dipahami karena keunikan karakternya. Permasalahan muncul ketika dosen masih menerapkan pengajaran konvensional yang mengakibatkan ketidakpuasan pembelajar milenial di kelas. Oleh karena itu, dosen dihadapkan dengan tantangan merubah gaya mengajarnya untuk memenuhi kebutuhan milenial di dalam kelas. Tujuan penelitian ini untuk menganalisa gaya komunikasi dalam pengajaran dosen menggunakan model kolaborasi yang dinilai berdasarkan pesepektif para mahasiswa milenial. Universitas Telkom dipilih sebagai lokasi penelitian atas dasar prestasinya sebagai predikat kampus swasta terbaik di Indonesia yang memperoleh pengakuan akreditasi internasional bergengsi. Para informan yang berpartisipasi adalah 30 mahasiswa kelas internasional berusia 18-19 tahun pada semester pertama. Penulis melakukan diskusi terumpun yang direkam melalui online zoom. Hasil penelitian menemukan bahwa gaya pembelajar milenial menginginkan pengalaman intelektual, pengalaman emosional dan pengalaman teknologi melalui gaya belajar kolaboratif dalam aktivitas pembelajaran mereka. Selain itu, mereka menyenangi dosen yang melakukan gaya komunikasi mengajar dengan penuh humor, interaktif, menggunakan aplikasi video dan mampu memahami minat mereka. Dengan menerapkan 3 pengalaman belajar milenial melalui model kolaborasi dan gaya komunikasi dosen mengajar tersebut akan meningkatkan partisipasi aktif pembelajar milenial.Kata Kunci: Komunikasi, model kolaborasi, gaya pengajaran, pembelajar milenial